Analisis Kepuasan Konsumen dan Efisiensi Biaya Usahatani Bawang Merah (Allium Ascalonicum L) di Kebun Praktek Fakultas Teknologi Pangan Pertanian dan Perikanan - Rafani, Antonieta (Peneliti.net, 2024)
Satisfaction is an assessment of the characteristics or features of a product or service, or the product itself, which provides a level of consumer pleasure related to fulfilling consumer consumption needs. Consumer satisfaction can be created through quality, service and value. Consumer satisfaction is an important factor that contributes to indicators of creating consumer repurchases and consumer loyalty. The aim of this research is to determine the level of consumer satisfaction and cost efficiency of shallot farming in the Nusa Nipa University practice garden. The analytical method used is the descriptive method, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Sampling was carried out using the Accidental Sampling method. The research results show that: 1). The CSI calculation for shallot consumers at the Nusa Nipa University Practice Garden was 0.812 (81.2%). If you pay attention to the CSI value obtained, it is in the satisfaction index range of 0.81 – 1.00, which means that the level of consumer satisfaction for shallot products is at the level of very satisfied with the performance of the attributes of shallot products in the Nusa Nipa University Practice Garden. 2). the percentage of production cost efficiency in 2023 is 83.33%. Realization of production costs can be said to be efficient because the amount of production costs that must be incurred is actually smaller than the budget.